Optimizing of operation strategies of the single-stage partial nitrification-anammox process. (20th May 2020) - Chen, Guangjiao; Zhang, Yanlong; Wang, Xingfa; Chen, Feng; Lin, Lan; Ruan, Qizhen; Wang, Yuzheng; Wang, Feifei; Cao, Wenzhi; Chiang, Penchi
Abstract: To achieve efficient and stable nitrogen removal and low N2 O emission in the single-stage partial nitrification (PN)-anaerobic ammonium oxidation (anammox) process, a sequence batch reactor (SBR) was operated for 223 days, the optimal operation strategies were investigated. Aeration rate control was applied to achieve the synergy between anammox and partial nitrification. The variation of specific anammox activity (SAA), specific ammonia oxidizing bacteria activity (SAOA), and specific nitrite oxidizing bacteria activity (SNOA) revealed that the anammox process was a rate-limiting step under low-strength ammonium loading condition. With the long-term acclimation, the anammox process showed more tolerance to substrate variation, in contrast, the inhibitory threshold concentration of partial nitrification to ammonium was decreased. The evolution of specific activities and substrate tolerance abilities of the functional microbes verified the changes in the nitrogen removal performance and proved that the aeration control strategy was efficient for operating a low nitrogen loading PN-anammox reactor. The nitrous oxide (N2 O) isotopic composition analysis revealed that 73% of N2 O was produced via the nitrifier denitrification pathway. N2 O production could be mitigated by increasing the SAA in the PN-anammox process. The reveal of the synergy effect between functional microbes and the N2 O pathway provide a guidance for operating a PN-anammox system for treating low nitrogen loading wastewater. Graphical abstract: Image 1028 Highlights: Aeration control is efficient for operating PN-anammox system with low NLR. The anammox process is a rate-limiting step under low NLR. The substrate tolerance ability of AnAOB was significantly improved. Nitrifier denitrification is the dominant pathway of N2 O production.